2004
DOI: 10.1097/00054725-200401000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA Damage in the Mucosa of Ulcerative Colitis Increases With Disease Duration and Dysplasia

Abstract: Oxidative DNA damage accumulates with the duration of the disease in ulcerative colitis reaching maximal increase if dysplastic lesions are found with possible implications for mutagenic and carcinogenic progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 22 publications
3
66
0
3
Order By: Relevance
“…A relação entre estresse oxidativo e inflamação já foi anteriormente descrita, quando se verificou aumento na intensidade de dano oxidativo ao DNA quanto mais duradouro e intenso fosse o processo inflamatório, determinando o aparecimento de lesões displásicas possivelmente relacionadas ao surgimento do câncer. 31 Estudos experimentais demonstraram que em camundongos silenciados para o gene Il-10, aproximadamente 60% deles desenvolveram tumores no cólon proximal após um período inicial de intenso processo inflamatório na mucosa cólica. 32 Da mesma forma, 30% dos camundongos silenciados simultaneamente para os genes Il-2 e b2 microglobulina desenvolveram adenocarcinoma no cólon, após longo período de exuberante processo inflamatório, com ín-dices de mutações nos genes APC e p53 de 100 % e 60% respectivamente.…”
Section: Figura 4 -Formação De 8ohdg Pelas Espécies Livres De Oxigêniunclassified
“…A relação entre estresse oxidativo e inflamação já foi anteriormente descrita, quando se verificou aumento na intensidade de dano oxidativo ao DNA quanto mais duradouro e intenso fosse o processo inflamatório, determinando o aparecimento de lesões displásicas possivelmente relacionadas ao surgimento do câncer. 31 Estudos experimentais demonstraram que em camundongos silenciados para o gene Il-10, aproximadamente 60% deles desenvolveram tumores no cólon proximal após um período inicial de intenso processo inflamatório na mucosa cólica. 32 Da mesma forma, 30% dos camundongos silenciados simultaneamente para os genes Il-2 e b2 microglobulina desenvolveram adenocarcinoma no cólon, após longo período de exuberante processo inflamatório, com ín-dices de mutações nos genes APC e p53 de 100 % e 60% respectivamente.…”
Section: Figura 4 -Formação De 8ohdg Pelas Espécies Livres De Oxigêniunclassified
“…4,5 Ulcerative colitis provides an example of chronic inflammation resulting in an accumulation of oxidative DNA damage. D'Inca et al reported that longer duration of ulcerative colitis resulted in increased levels of 8-hydroxyguanosine , an oxidative DNA adduct, 6 possibly explaining why the risk of developing colorectal cancer from colitis increases by 0.5-1.0% every year after 7 years of disease. 7 Additionally, excess ROS because of chronic inflammation may result in oxidative modification of proteins leading to inappropriate activity of regulatory pathways important in the progression of carcinogenesis.…”
mentioning
confidence: 99%
“…This condition leads to an increased risk of carcinogenesis. In line with this hypothesis, D'Inca recently showed that the maximum level of the oxidative DNA damage can be found in lesions with carcinogenic progression [3,24]. Concurrently, it was shown by Martinez et al [25] that RNS may also induce colon carcinogenesis.…”
Section: Dysregulation Of Oxidation Pathwaysmentioning
confidence: 89%
“…Oxidative stress-related pathways are a possible cause of IBD and they also play a major role in the transformation of IBD into CACRC [24]. The amount of phagocytic leukocytes is increased in IBD patients, mainly in UC patients, what results in an enhanced production of pro-oxidant molecules.…”
Section: Dysregulation Of Oxidation Pathwaysmentioning
confidence: 99%